Whale Shark in The Development of Geopark and Sustainable Tourism in Gorontalo, Indonesia - Umar Adisubroto; Togu S. Pardede (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
The whale shark (Rhincodon typus, Hiu Paus), the world's largest type of fish/mammal presents in Indonesia, in Botubarani, Gorontalo province, among others. This province is actively developing geoparks which are currently still aspiring geopark status, as well as tourism, and making whale sharks its icon. Our paper studies the development of whale sharks as a marker of the area's biodiversity, to promote it as a more common activity in Indonesia where whale sharks can be found. We support strategic ideas for the development of whale sharks and formulate several recommendations for geotourism activities where whale sharks are icons.